Pendampingan Siswa SMK Pemasaran Dalam Menemukan Ide Bisnis dan Strategi Pemasaran Digital yang Legal dan Halal - Akbar, Jodi Septiadi; Wisdawati, Ramadhana Aulia; Arifin, Iqbal Maulana (Abdimas Mandalika, 2026)
Abstract:  The rapid expansion of the digital economy demands that the younger generation, particularly Vocational High School (SMK) students, cultivate entrepreneurial skills that are creative, innovative, and grounded in legal and halal principles. This community service program aims to strengthen SMK students' competencies in developing business ideas and implementing digital marketing strategies aligned with legal compliance and halal ethics. The program was executed through four integrated stages: (1) product innovation and branding strategy training using a design thinking approach; (2) business legality education via the OSS RBA online platform; (3) digital marketing literacy utilizing social media; and (4) entrepreneurial mini-projects and evaluation. Results indicate improved student capabilities in formulating 11–14 realistic business ideas, understanding business legal aspects such as Business Identification Number (NIB) registration procedures, and applying digital marketing strategies consistent with halal business ethics. Ultimately, this program is expected to foster a sustainable entrepreneurial spirit and contribute to the development of the creative economy among vocational high school students.Abstrak: Perkembangan pesat ekonomi digital menuntut generasi muda, khususnya siswa Sekolah Menengah Kejuruan (SMK), untuk menumbuhkan keterampilan kewirausahaan yang kreatif, inovatif, dan berlandaskan prinsip legal dan halal. Program pengabdian masyarakat ini bertujuan untuk memperkuat kompetensi siswa SMK dalam mengembangkan ide bisnis dan menerapkan strategi pemasaran digital yang selaras dengan kepatuhan hukum dan etika bisnis halal. Program ini dilaksanakan melalui empat tahapan terintegrasi: (1) pelatihan inovasi produk dan strategi branding menggunakan pendekatan design thinking; (2) edukasi legalitas usaha melalui platform daring OSS RBA; (3) literasi pemasaran digital memanfaatkan media sosial; dan (4) proyek mini kewirausahaan dan evaluasi. Hasil kegiatan menunjukkan peningkatan kemampuan siswa dalam merumuskan 11–14 ide bisnis yang realistis, memahami aspek legal usaha seperti prosedur pendaftaran Nomor Induk Berusaha (NIB), serta menerapkan strategi pemasaran digital yang konsisten dengan etika bisnis halal. Pada akhirnya, program ini diharapkan dapat menumbuhkan semangat kewirausahaan yang berkelanjutan dan berkontribusi terhadap pengembangan ekonomi kreatif di kalangan siswa sekolah kejuruan.